2006
DOI: 10.1002/ca.20404
|View full text |Cite
|
Sign up to set email alerts
|

Extraocular eye muscles in human fetuses with craniofacial malformations: Anatomical findings and clinical relevance

Abstract: Anomalies of the extraocular muscles have been suspected to be present frequently in patients with craniofacial malformations. We studied the extraocular musculature in the orbits of 15 anencephalic human fetuses between the 5th and 10th months after gestation, and in one fetus with an occipital meningocele and a large defect of the left cranial base. The findings were compared to those in nine normal age-matched fetuses. All malformed fetuses exhibited special features of the levator palpebrae superioris musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The normal muscles do not make a cluster but are distributed at the proper sites in the size of the present specimen (Osanai et al, 2010). The extraocular muscles and bony cranium develop simultaneously (Plock et al, 2007). However, previous references did not refer to the orbital muscle, a smooth muscle that was well developed in the present specimen.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The normal muscles do not make a cluster but are distributed at the proper sites in the size of the present specimen (Osanai et al, 2010). The extraocular muscles and bony cranium develop simultaneously (Plock et al, 2007). However, previous references did not refer to the orbital muscle, a smooth muscle that was well developed in the present specimen.…”
Section: Discussionmentioning
confidence: 74%
“…In contrast, the causes of restricted abnormalities are difficult to determine. Plock et al (2007) described and reviewed anomalies of human extraocular muscles. Abnormal extraocular muscles often appear in combination with common craniofacial anomalies such as Crouzon, Apert, Pfeiffer, and Goldenhar-Gorlin syndromes (in short, these syndromes include anomalies of the mandible, eye, and other parts of the body such as the hand and fingers).…”
Section: Introductionmentioning
confidence: 99%
“…Variations of the LPS muscle may also cause congenital blepharoptosis. This pathological condition usually occurs as an isolated defect in otherwise healthy children, although it may be associated with craniofacial malformations and ocular mobility disorders 13 . Baldwin and Manners's study centred on distinguishing whether the reason of the disease should be classified as a dystrophy (inherited disease with progressive muscle weakness and wasting) or a dysgenesis (a defect in the development of the muscle) and showed that available histological data appeared to support the classification of congenital blepharoptosis as a dysgenic phenomenon 14…”
Section: Discussionmentioning
confidence: 99%
“…Variations of the LPS may also cause congenital blepharoptosis. This pathological condition usually occurs as an isolated defect in otherwise healthy children, although it may associated with craniofacial malformation and ocular motility disorder (14) .…”
Section: Discussionmentioning
confidence: 99%
“…Amonoo-Kuofi and Darwish (1998) reported bilateral accessory LPS muscle between superior oblique and LPS that ran from the lessser wing of the sphenoid to the skin of the upper lid, but these muscle were not bipartite (9) . Fetal LPS exhibit a broad aponeurotic insertion on the upper lid and the connective tissue of the lacrimal gland, often with medial and lateral accessory muscular slips or fibrous bands arising from LPS (Plock et al 2005) (10) . Changes during embryogenesis upto 24 months postnatally may result in LPS undergoing adaptation (11) .…”
Section: Discussionmentioning
confidence: 99%